Pembinaan Manajemen Peserta Didik dalam Perspektif Islam - Anggi Anggraini; Fauzan Azhima Sirait; Nurdahyanti Nurdahyanti; Syahpan Ramadhan (Journal on Education, 2023)
Student coaching is one way to carry out student management functions. In general, student development is an activity aimed at developing the potential of students in accordance with national educational goals. Student management is the arrangement and arrangement of activities related to students, starting from the student entering to leaving a school.Wahjosumidjo in his book states that Coaching is an effort, or activity that provides guidance, direction, strengthening, improvement, direction towards the mindset, mental attitude, behavior and interests, talents and skills of the students. The development of students is also put forward its definition according to Soetjipto and Raflis Kosasi Soetjipto and Raflis is the provision of services to students in an educational institution, both inside and outside his study hours in class. In line with Wahjosumidjo student development, namely efforts or activities to provide guidance, direction, strengthening, improvement, direction to the mindset, mental attitudes, behaviors and interests, talents and skills of students, through extracurricular programs in supporting curricular success.